Association of Pulse Pressure with Serum TNF-α and Neutrophil Count in the Elderly - Eriko Yamada; Mika Takeuchi; Miki Kurata; Tsutomu Kazumi; Keisuke Fukuo (Journal of Diabetes Research)
Aims. Elevated pulse pressure (PP) has been reported to be a risk factor for type 2 diabetes in elderly patients with hypertension. Methods. Cross-sectional relationships of PP with known risk factors for type 2 diabetes and inflammatory markers were examined in 150 elderly community-dwelling women, 79 women (52.7%) of whom had hypertension. Results. Systolic blood pressure (standardized β, 0.775), log tumor necrosis factor-α (TNF-α, standardized β, 0.110), age (standardized β, 0.140), and neutrophil count (standardized β, 0.114) emerged as determinants of PP independent of high-sensitivity C-reactive protein, interleukin-6, monocyte count, plasminogen activator inhibitor-1, homeostasis model assessment of insulin resistance, HDL-cholesterol, and adiponectin (R2 = 0.772). Conclusions. The present studies have demonstrated an independent association of higher PP with higher TNF-α, a marker of insulin resistance, and neutrophil count in community-living elderly women and suggest that insulin resistance and chronic low-grade inflammation may in part be responsible for the association between high PP and incident type 2 diabetes found in elderly patients with hypertension.